Réponses

2013-05-11T15:34:20+02:00

A = (x+1) [(x+2) + (x+3)]

A = (x+1) (x+2+x+3)

A = (x+1) (2x+5)

 

B = (x-1) [(1-2x) - (x+6)]

B = (x-1) (1 - 2x - x - 6)

B = (x+1) (-3x-7)

 

C = (2x+1) [(x-2) - (2x+1)]

C= (2x+1) (x-2 - 2x - 1)

C = (2x+1) (-x - 3)

Meilleure réponse !
2013-05-11T15:37:10+02:00

A = (x + 1)(x + 2) + (x + 1)(x + 3)

A = (x + 1) [(x + 2) + (x + 3)]

A = (x + 1)(x + 2 + x + 3)

A = (x + 1)(2x + 5)

 

B = (1 - 2x)(x - 1) - (x + 6)(x - 1)

B = (x - 1) [(1 - 2x) - (x + 6)]

B = (x - 1)(1 - 2x - x - 6)

B = (x - 1)(-3x - 5)

 

C = (2x + 1)(x - 2) + (2x + 1) - (2x + 1)

C = (2x + 1)[(x - 2) - (2x - 1)] 

C = (2x + 1)(x - 2 - 2x + 1)

C = (2x + 1)(-x - 1)